The Impact of Visual AIDS on English Language Learning Among Secondary School Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the impact of visual aids on students' learning outcomes in English as a Foreign Language (EFL) classrooms. Drawing on classroom-based experiments with secondary school students, it compares traditional methods with those enhanced by visual materials. Results show that visual aids significantly boost motivation, participation, and comprehension, particularly in grammar and vocabulary acquisition.